Determinação de parâmetros ótimos no processo de deságue em peneiras vibratórias - Barbosa, Rafael Yuri Medeiros (2021)
The main objectives of the solids control stage in the oil industry are to recover the drilling fluid to reuse it in the process and adapt the solid material for safe disposal, in compliance with current environmental laws. In the solids control step, shale shakers are the first equipment used and this equipment has the function of recovering as much drilling fluid as possible, thus reducing the fluid content of the residual solid for the other steps of the solids control system . As this is the first equipment in solids control, the optimized operation of shale shakers optimizes the entire solids control process. This work presents a proposal of a mathematical model of phenomenological basis that describes the operation of a shale shaker, and it also presents simulations for a scenario of solid-free feeding, experimental results obtained in an industrial-scale vibratory sieve and optimal operating parameters that reduce the liquid content of the solid material. The results indicated that longer residence times of the material on the shale shaker screen favor the reduction of the liquid content in the residual solid.